Feeding problem as the risk factors for stunting among under five children in Kuantan – a case control study - Kamaruzaman, Nor Azam; Musa, Noraini; Pasi, Hafizah; Osman, Iskandar Firzada (Malaysian Public Health Physicians' Association, 2022)
Feeding problem in under five children may lead to stunting which is the most prevalent form of malnutrition in this age group. This case-control study was conducted on a total of 40 children aged 6 to 59 months diagnosed with stunting and 120 children with normal height-for-age. In general, children with any feeding problem have more than four-time significantly higher risk of becoming stunted as compared to children with no feeding problem. Children with inadequacy in feeding components specifically frequency, variety and amount of meal each have significantly higher risk of becoming stunted as compared to children with adequate feeding.